Return to training in soccer players after anterior cruciate ligament reconstruction: reflections and considerations - Alashram, A. R.; D`Onofrio, R.; Sannicandro, I.; Manzi, V.; Padua, E.; Youssef, T.; Annino, G. (The Journal of Sports Medicine and Physical Fitness, 2024)
This clinical and rehabilitative overview focuses on the return to unrestricted sporting activity, aiming to consolidate the scientific evidence surrounding the structural progression of athletes, particularly footballers, undergoing anterior cruciate ligament reconstruction (ACLR). A multidisciplinary approach necessitates a shared language and standardized methodologies. Unfortunately, significant disparities persist in the structural strategies guiding the decision-making process for returning to on-field activities, the latter stages of rehabilitation, and subsequent restoration of technical and tactical football abilities. Divergences in definitions, terminologies, and rehabilitation protocols can substantially influence final outcomes. Presently, scientific consensus studies regarding the decision-making process during the final stages of on-field rehabilitation are lacking. Nevertheless, this overview outlines and defines pivotal language parameters crucial for effective communication and the seamless integration of clinical and rehabilitative data among the diverse professionals involved in facilitating the athlete`s return to peak performance. In conclusion, the successful resumption of competitive sporting activities for footballer`s post ACLR demands a collaborative decision-making approach encompassing various professionals. Additionally, it necessitates a cohesive transition from rehabilitation to on-field work, aiming at reinstating athleticism, technical prowess, and tactical acumen.